Progress on oxidative stress and natural phytogenic antioxidants in dairy cows - LI Yongxin; ZOU Yixuan; LIU Jianxin; LIU Hongyun (浙江大学学报. 农业与生命科学版)
Oxidative stress has a negative impact on production performance, reproductive performance and disease resistance of dairy cows. It is particularly serious for high-producing dairy cows. The occurence of oxidative stress is closely related to the physiological stage, nutritional status and environmental temperature of dairy cows. At present, the common practice to prevent and relieve oxidative stress is to add vitamins, trace elements and plant extracts to the diets for cows. This review summarized the causes and harm effects of oxidative stress on dairy cows, as well as the antioxidant measures and their mechanisms, aiming to provide theoretical basis for antioxidant mechanism research and novel antioxidant exploitation in dariy cows.